Creating A Competitive Advantage For Universities Through Knowledge-Based Strategic Assets Management - Istikhoroh, Siti; Rachma Ardhiani, Mutiara (KnE Social Sciences, 2022)
This study aims to identify and analyze strategic assets for universities and explain the role of leadership in maximizing the use of these assets as a competitive advantage through knowledge management practices. As a non-profit organization, universities live in a competitive world of higher education services. Theoretical and practical studies prove that intense competition will be won by organizations that have a sustainable level of competitive advantage, not temporary competitive advantages. In order to identify strategic assets for higher education institutions, this study assumes that all knowledge-based assets are strategic assets that add value to the organization and improve organizational performance. The role of higher education as a knowledge-based organization that nurtures diverse knowledge and as a producer of reliable human resources in the scientific field establishes knowledge-based assets or intellectual capital as the strategic capital of universities. The research population are the leaders of universities in East Java, both state universities and private universities. The sample was determined based on the purposive random sampling technique, namely by selecting the leaders of universities with a rating (AIPT) of at least B or Good, totalling 113 people. The criteria are set with the assumption that the university leadership has implemented knowledge management. Data were collected by distributing questionnaires and analyzed using SEM-PLS. Research is useful both theoretically and practically. At the theoretical level, a strategy for managing intellectual capital is formulated as a strategic asset, while at the practical level it can be carried out by university leaders. Keywords: Intellectual Capital, Knowledge Management, AIPT, Competitive Advantage